Efficiency of Islamic banks during the financial crisis: An analysis of Middle Eastern and Asian countries - Rosman, Romzie (Elsevier B.V., 2013)
The world economy is still suffering from the severe global financial crisis that caused the failure of several banks.This has encouraged economists worldwide to consider alternative financial solutions and attention has been focused on Islamic banking and finance as an alternative model.Hence, this study examines the efficiency level of Islamic banks during the financial crisis specifically in Middle Eastern and Asian countries from 2007 to 2010.Moreover, bank-specific and risk factors were examined to understand the determinants of efficiency. The efficiency of Islamic banks is measured using data envelopment analysis by adopting the intermediation approach.The financial information is extracted from BankScope database for a four year period (2007–2010) which includes 79 Islamic banks across a number of countries.The study also critically analyses pure technical efficiency and scale efficiency of the Islamic banks in Middle Eastern and Asian countries and estimates their return to scale.The findings explain that Islamic banks were able to sustain operations through the crisis.However, the study also shows the majority of these Islamic banks were scale inefficient. Most of the scale inefficient banks were operating at decreasing returns to scale.This study also found that both profitability and capitalisation were the main determinants of Islamic banking efficiency.Hence, the findings of this study have policy implications and make a contribution to policy-making by providing empirical evidence on the performance of the Islamic banks and their efficiency levels.